Characterisation of the Cullin‐3 mutation that causes a severe form of familial hypertension and hyperkalaemia - Schumacher, Frances‐Rose; Siew, Keith; Zhang, Jinwei; Johnson, Clare; Wood, Nicola; Cleary, Sarah E; Al Maskari, Raya S; Ferryman, James T; Hardege, Iris; Yasmin; Figg, Nichola L; Enchev, Radoslav; et al. (EMBO molecular medicine, 2015)
Deletion of exon 9 from Cullin‐3 (CUL3, residues 403–459: CUL3 Δ403–459 ) causes pseudohypoaldosteronism type IIE (PHA2E), a severe form of familial hyperkalaemia and hypertension (FHHt). CUL3 binds the RING protein RBX1 and various substrate adaptors to form Cullin‐RING‐ubiquitin‐ligase complexes. Bound to KLHL3, CUL3‐RBX1 ubiquitylates WNK kinases, promoting their ubiquitin‐mediated proteasomal degradation. Since WNK kinases activate Na/Cl co‐transporters to promote salt retention, CUL3 regulates blood pressure. Mutations in both KLHL3 and WNK kinases cause PHA2 by disrupting Cullin‐RING‐ligase formation. We report here that the PHA2E mutant, CUL3 Δ403–459 , is severely compromised in its ability to ubiquitylate WNKs, possibly due to altered structural flexibility. Instead, CUL3 Δ403–459 auto‐ubiquitylates and loses interaction with two important Cullin regulators: the COP9‐signalosome and CAND1. A novel knock‐in mouse model of CUL3 WT /Δ403–459 closely recapitulates the human PHA2E phenotype. These mice also show changes in the arterial pulse waveform, suggesting a vascular contribution to their hypertension not reported in previous FHHt models. These findings may explain the severity of the FHHt phenotype caused by CUL3 mutations compared to those reported in KLHL3 or WNK kinases. Synopsis Molecular defects observed in a mutant form of the ubiquitin E3 protein CUL3 causing a severe form of familial hypertension (PHA2E) result in E3 ligase loss of function. A novel mouse model with the same CUL3 disease mutation was generated, and it closely recapitulates the human PHA2E phenotype. Mutations in CUL3 that cause hereditary hypertension prevent the ubiquitylation and degradation of WNK kinases probably due to increased flexibility of the cullin backbone. The mutant CUL3 Δ403–459 protein shows marked auto‐ubiquitylation and loss of binding to the critical cullin regulators, CSN and CAND1. The phenotype of knock‐in mice carrying the CUL3 Δ403–459 mutation closely recapitulates PHA2E; kidney DCTs contain striking accumulation of WNK and SPAK proteins. The mice expressing CUL3 Δ403–459 have a vascular phenotype suggesting increased vascular tone that may contribute to the severity of the hypertension seen in PHA2E compared to other forms (PHA2A‐D). Graphical Abstract Molecular defects observed in a mutant form of the ubiquitin E3 protein CUL3 causing a severe form of familial hypertension (PHA2E) result in E3 ligase loss of function. A novel mouse model with the same CUL3 disease mutation was generated, and it closely recapitulates the human PHA2E phenotype.